2012
DOI: 10.4103/0971-4065.86408
|View full text |Cite
|
Sign up to set email alerts
|

Cortical blindness in a child with acute glomerulonephritis

Abstract: The association between hypertensive encephalopathy and cortical blindness in children with acute glomerulonephritis is extremely rare. We report the case of a 9-year old girl who presented with headache, seizures, altered sensorium, hematuria, and transient cortical blindness as a complication of hypertensive encephalopathy which showed complete reversal following normalization of blood pressure and an underlying post-infectious acute glomerulonephritis was revealed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…[ 1 ] Literature consists of few case reports or few small series of patients in different clinical settings. [ 1 2 3 4 5 6 7 ] All age groups are susceptible to the syndrome. The setting in which it was described included patients with hypertensive encephathalopathies, patients who were receiving immunosuppressive medicines after organ transplantation or other malignancies, patients with renal failure, and patients with eclampsia.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] Literature consists of few case reports or few small series of patients in different clinical settings. [ 1 2 3 4 5 6 7 ] All age groups are susceptible to the syndrome. The setting in which it was described included patients with hypertensive encephathalopathies, patients who were receiving immunosuppressive medicines after organ transplantation or other malignancies, patients with renal failure, and patients with eclampsia.…”
Section: Introductionmentioning
confidence: 99%
“…Gupta et al reported that PSGN with PRES presented with hypertension, transient vision loss with computed tomography of brain findings, which was reversed after hypertension control [13]. Kaarthigeyan and Vijayalakshmi reported a case with typical PSGN features and transient blindness [15].…”
Section: Discussionmentioning
confidence: 99%
“…Subklinik APSGN çoğunlukla hastaların aile yakınları veya yakın temasta oldukları kimselerde tanımlanmaktadır (20,23) . (3,8,20,(24)(25)(26) .…”
Section: çOcuk Vakalardaki Daha Ender Apsgn Başvuru Kliniğiunclassified